Overweight and obesity in children and adolescents, 2016 Halfway National Health and Nutrition Survey update - Teresa Shamah-Levy; Lucía Cuevas-Nasu; Elsa Berenice Gaona-Pineda; Luz María Gómez-Acosta; María. del Carmen Morales-Rúan; Mauricio Hernández-Ávila; Juan Ángel Rivera-Dommarco (Instituto Nacional de Salud Pública, 2018)
Objective. To estimate recent overweight and obesity prevalences in Mexican population under 20 years from Halfway National Health and Nutrition Survey (Ensanut MC 2016). Materials and methods. Ensanut MC 2016 is a probabilistic national survey which gives representative information from national, regional and rural/urban levels. BMIz was estimated through weight and height, then it was classified into overweight risk or overweight or obesity according to WHO growth reference standards. Association between overweight and sociodemographic information was analyzed through logistic regression models. Results. Overweight-obesity prevalence was 5.1% in girls and 6.5% in boys<5y, 32.8% in girls and 33.7% in boys 5-11y, and 39.2% in female adolescents and 33.5% in male adolescents. Female adolescents from rural localities increased overweight-obesity prevalence from 27.7% in 2012 to 37.2% in 2016. Conclusions. Overweight-obesity increased in girls and females, mainly from rural areas. Strategies focued in containing this phenomenon are encouraged to implement in this context.